Trace determination of organophosphate esters in environmental water samples with an ionogel‐based nanoconfined ionic liquid fiber coating for solid‐phase microextraction with gas chromatography and flame photometric detection. Issue 22 (8th November 2016) - Pang, Long; Pang, Rong; Ge, Liming; Zheng, Liqing; Zhao, Jihong; Zhang, Hongzhong
Abstract : Organophosphate esters, widely used as flame retardants and plasticizers, are regarded as a class of emerging pollutants. In this work, a novel approach was developed for the fabrication of a solid‐phase microextraction fiber by using hybrid silica‐based materials with immobilized ionic liquids with sol–gel technology, and the prepared solid‐phase microextraction fiber was then coupled with gas chromatography and flame photometric detection for the analysis of six organophosphate esters. The high loading of 1‐hexadecyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide was confined within the hybrid network. The developed solid‐phase microextraction fiber possesses a coating thickness of ∼35 μm with good thermal stability and long lifetime. The parameters affecting the extraction efficiency such as extraction time, temperature, pH, and ionic strength of the sample solution were optimized. Under the optimized conditions, the limits of detection were in the range of 0.04−0.95 μg L −1, and the precision of the method assessed with repeatability and reproducibility of (RSD%) ˂13 and ˂29%, respectively. The proposed method was successfully applied to determine the six organophosphate esters in three real water samples, with recoveries in the range of 64.8−125.4% at two different spiking concentration levels. As a result, the proposed method demonstrated its potential for application in trace determination of organophosphate esters in actual water samples.